2018
DOI: 10.1007/s40195-018-0702-z
|View full text |Cite
|
Sign up to set email alerts
|

Design of Fe–Mn–Ag Alloys as Potential Candidates for Biodegradable Metals

Abstract: In this work, a series of biodegradable pure iron, Fe-30Mn and Fe-30Mn-Ag alloys were developed by using a rapid solidification technology. A fine a-Fe dendrite was formed in pure iron, resulting in a high compressive yield strength of above 300 MPa. The Fe-30Mn alloy doped with only 1% Ag exhibited a significant increase in the degradation rate in simulated body fluid due to the precipitation of Ag-rich particles in alloy matrix and the induction of the microgalvanic corrosion. In addition, the novel Fe-30Mn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 31 publications
4
36
0
Order By: Relevance
“…As manganese shifts the free corrosion potential to the less noble values, alloying with iron increases the corrosion rate [40]. Silver addition was found to form Ag-rich particles within the Fe-Mn matrix that gives a microgalvanic effect thus accelerating corrosion [15,16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…As manganese shifts the free corrosion potential to the less noble values, alloying with iron increases the corrosion rate [40]. Silver addition was found to form Ag-rich particles within the Fe-Mn matrix that gives a microgalvanic effect thus accelerating corrosion [15,16].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, the shallow depth of ion implantation (~60 nm) only provided those desirable effects on the thin surface and for a short period. Liu et al [15] developed a Fe-30Mn-1Ag alloy using a rapid solidification technique and found that the alloy corroded faster in simulated body fluid due to the microgalvanic effect of the Ag-rich particles with the Fe-Mn matrix. Similar microgalvanic effect of silver addition to accelerating corrosion was observed by Wiesner et al [16] on Fe-Mn-Ag alloys prepared by selective laser melting from mixed powders of Fe-Mn and Ag.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have focused on increasing the corrosion rate of pure iron by alloying [3, 7, 10] and the creation of microgalvanic couples through the use of noble elements [11, 12]. Addition of Mn to Fe has the effect of reducing the overall corrosion resistance of the alloy when exposed to in vitro solutions which simulate the in vivo scenario [3, 7, 10].…”
Section: Introductionmentioning
confidence: 99%
“…[13] show that pure iron had a corrosion rate of 14 μA/cm 2 in modified Hank's solution and this rose to 105.6 μA/cm 2 in the same electrolyte when 35% Mn was added to the sample composition. The addition of cathodic elements such as palladium and silver increases the corrosion rate of pressed and sintered iron based alloys, and this increase is attributed mainly to the galvanic effect of the cathodic element inclusions on the Fe–Mn grains [11, 12]. However, it is observed that with palladium, the increase in corrosion was not accompanied by an increase in the mass of material lost from the alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the twenty-first century, biodegradable metals represent a new generation of biomedical materials used as temporary implants in vascular intervention or osteosynthesis [1,2]. These novel biodegradable metals have revolutionized the traditional idea of permanent devices, avoiding persistent physical irritation, chronic inflammation, the need for prolonged anti-platelet aggregation therapy, and possible surgery for removing the implant [3].…”
Section: Introductionmentioning
confidence: 99%